Penerapan Prinsip Due Care Oleh Produsen Terhadap Peredaran Obat Di Masyarakat - Amtsal, Abdul; Pesulima, Theresia Louize; Balik, Agustina (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: Due care principle or the principle of prudence is a principle that must be applied by producers in producing goods or services in order to ensure that the products produced are really safe for consumption.Purposes of the Research: The purpose of this study is to find out and explain the application of the due care principle by manufacturers to the circulation of drugs in the community as well as the responsibility of manufacturers for syrup drugs containing harmful compounds.Methods of the Research: The research method used in this writing is a normative juridical research method with a legislative approach, a case approach and a conceptual approach, to answer the problems raised.Results of the Research: The results of this study can be concluded that the application of the Due Care Principle by manufacturers to drug circulation in the community underlines the importance of manufacturers being more careful in maintaining quality and safety in producing and distributing drugs. This includes testing and surveillance, reporting and transparency, distribution chains, and vigilance against contamination of a drug product. And manufacturers who produce syrup drugs containing harmful compounds can be requested strict liability based on Article 19 of the Consumer Protection Law.